From Wellington to Quebec: Attracting Hollywood and Regulating Cultural Workers - Choko, Maude; Conor, Bridget (Relations industrielles / Industrial Relations, 2017)
The nature of work arrangements in the film industry and the professional characteristics of cultural workers involved in film production impact the legal qualification of these workers. They highlight the difficult task of classifying actual work arrangements in one specific legal category: either an “employment relationship” or a “contract for services relationship”. If adequate legal frameworks are not in place to capture the reality of those work arrangements properly, the legal qualification may lead to uncertainty detrimental to workers’ access to collective representation. This uncertainty opens the door to work conflicts and contestations of different types. This paper builds a dialogue between two disciplines, legal analysis and cultural labour analysis, by comparing two locally embedded case studies: the “Hobbit Law” in New Zealand and the “Spiderwick Case” in Quebec (Canada).Firstly, we outline our theoretical and methodological approach, drawing on literature on cultural labour studies as well as legal analysis. Secondly, we compare the legal status of cultural workers and collective representation within each of our cases. Thirdly, we present full accounts of the chronology, conflicts and contestations within our two cases, as well as outlining the legislative outcomes in each. And finally, in comparing these cases, we illustrate the difficulty of legally qualifying these relations, the uncertainty this engenders and the differing impacts these difficulties have had on collective action in each industry. We emphasize that each case, with their vastly differing outcomes, provides evidence of both the inclusion of cultural workers within the boundaries of specific legislation fostering collective representation of artists (in the Spiderwick Case) and the exclusion of cultural workers from the boundaries of labour legislation enabling collective representation of employees (in the Hobbit Case). This is telling because these cases both took place in a location attracting Hollywood’s productions and, for both, this power of attraction remains crucial for the local industry. Understanding the impact of local cultural work regulation in the context of major global productions still lacks sustained attention and in this paper, we build a dialogue between our two cases to begin to remedy this.